The US PATRIOT Act (2001) - Buterbaugh, Kevin (Government at Work: Policymaking in the Twenty-First-Century Congress, 2016)
This edited volume features academic experts using leading policy frameworks to analyze the prominent U.S. public policy issues of the twenty-first century. Readers will learn about the similariti...
Keywords: dept.psc